Specific Absorption Rate Assessment of Multiple Microstrip Patch Antenna Array - Nur Ilham Aliyaa Ishak; Norhudah Seman; Noor Asmawati Samsuri (Universitas Ahmad Dahlan, 2018)
Interaction between electromagnetic field (EMF) radiated from multiple antennas and human body is crucial to be explored as multiple antennas are the essential implemented devices to achieve the requirements of the future evolved fifth generation (5G) technology. Thus, this article presents a significant study of the radiated EMF effect from a single, and multiple antennas towards human through the assessment of specific absorption rate (SAR). The single antenna, 1 x 2, 1 x 3 and 1 x 4 arrays of microstrip patch antennas are designed to cover mobile operating frequencies of 0.8, 0.85, 0.9, 1.8, 2.1 and 2.6 GHz. Two types of human head phantoms are implemented in this study, which are specific anthropomorphic mannequin (SAM) and Voxel head model that placed close to single antenna or antenna array to investigate the penetration of EMF towards the human tissue. The single antenna or antenna array is placed with fixed distance of 10 mm from the phantom, which excited by maximum allowable power of 19 dBm in CST Microwave Studio 2016. The effect of the radiated EMF that quantified by SAR parameter, which depicts satisfying results against the established standard limits at averaged 1g and 10g mass of tissues for all designated frequencies that utilized for single and multiple antennas.